2013
DOI: 10.1038/nature12791
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin signalling inhibitory fields provide robustness to phyllotaxis

Abstract: How biological systems generate reproducible patterns with high precision is a central question in science. The shoot apical meristem (SAM), a specialized tissue producing plant aerial organs, is a developmental system of choice to address this question. Organs are periodically initiated at the SAM at specific spatial positions and this spatiotemporal pattern defines phyllotaxis. Accumulation of the plant hormone auxin triggers organ initiation, whereas auxin depletion around organs generates inhibitory fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
277
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(298 citation statements)
references
References 54 publications
14
277
1
1
Order By: Relevance
“…S9, and Table S1) (32). Similar to leaf polarity, a recent report found that not one, but two, independent signaling mechanisms define phyllotaxis, the spatiotemporal pattern of leaves initiation at the meristem, leading to increased precision (46).…”
Section: Discussionmentioning
confidence: 92%
“…S9, and Table S1) (32). Similar to leaf polarity, a recent report found that not one, but two, independent signaling mechanisms define phyllotaxis, the spatiotemporal pattern of leaves initiation at the meristem, leading to increased precision (46).…”
Section: Discussionmentioning
confidence: 92%
“…The consequence of the auxin model [53,54] is that the new primordium at the shoot apex is initiated where the auxin concentration is sufficiently high. The possibility of modulating auxin concentrations by cytokinins and controlled expression of the genes such as PLETHORA or INDETERMINATE DOMAIN involved in auxin biosynthesis, transport and degradation is now being intensely studied [50,[66][67][68][69]. The area between adjacent inhibitory fields corresponds to Snow and Snow's first available space.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing quest for the mechanisms of robustness in phyllotaxis in experimental plant biology [49,50] is heavily affected by the fact of relative stability of the main Fibonacci in a model plant Arabidopsis thaliana. The major challenge then is to find out the level of noise that guarantees maintenance of the pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokinin signaling peaks in two bisymmetric procambial cell files, where it regulates the localization of PINFORMED (PIN) auxin efflux carriers and creates an auxin maximum in the adjacent xylem axis. Auxin signaling in turn promotes the expression of the negative regulator of cytokinin signaling AHP6 by ARF5 (Besnard et al, 2014). This mutually exclusive pattern of cytokinin and auxin is required for the specification of the bisymmetric vascular pattern (Bishopp et al, 2011).…”
Section: Mutually Exclusive Distribution Pattern Of Cytokinin and Auxmentioning
confidence: 99%